Volunteer economies : the politics and ethics of voluntary labour in Africa. - (:unkn) unknown (My University, 2019)
Worldwide, 'volunteerism' has become increasingly prominent in political ideologies, social movements, and individual experience. A volunteering ethic, voluntary labour, and volunteers are all central to global humanitarianism, development, philanthropy, and political activism for social justice, in both North-South and emerging South-South interventions. This review provides a critical analysis of a major book regarding volunteerism in Africa.
Keywords: African Research